Microfinance services and government regulations: Reflections on performance of small holder coffee entrepreneurs in Uganda - Mary Juliet Nakabugo; Stephen Muathe; Evans Mwasiaji (The Journal of Entrepreneurial Finance (JEF), 2022)
Small-scale enterprises are lauded around the world for their contribution to economic development. Resources and capabilities play an important role as accelerators of entrepreneurial activity and also increase enterprise performance. This research strived to understand how Microfinance services affect the performance of smallholder coffee entrepreneurs but also examine government regulations as a moderating variable for the association between microfinance and the performance of smallholder coffee entrepreneurs. The study was guided by the resource-based view supported by dynamic capability and contingency theories. Data on 400 Ugandan coffee entrepreneurs was gathered and statistically tested using a multiple linear regression model. Study scores noted that financial training, microcredit, saving mobilization, and farm inputs positively influence the performance of smallholder coffee entrepreneurs. The findings also established that government regulations negatively moderate the association between microfinance services and the performance of smallholder coffee entrepreneurs. The study contributes to the growing agricultural entrepreneurship literature by demonstrating the performance of coffee entrepreneurs amidst microfinance and strict government regulations.
Keywords: M; 650; Government Regulations; Microfinance services; Performance; Coffee Entrepreneurs; Uganda